Multimachine Stability Enhancement Using Fuzzy- Logic Based PSS Tuning With Shunt FACTS Device - Srishail K Bilgundi; M Madhusudhan; H Pradeepa; M V Likith Kumar (IAES Indonesian Section, 2023)
In Large power system network the dynamic behaviour of system is nonlinear in nature. Due to disturbance the system stability cannot be maintained, which leads to outage of power equipment. In order to restore the system parameter after perturbance, coordination control damping is essential. Coordination control damping can be achieved by using fuzzy based PSS and STATCOM in multimachine system for sever disturbance. Due to perturbance the system loss its synchronism and the system parameter deviate from the nominal value. With the effective damping control technique proposed in this article is to minimize the integral square error of speed deviation. Two area 4-Machine 11-bus test system considered and the simulation of proposed system is developed in Matlab/Simulink R2018a.